Legal and Political Philosophy - Villanueva, Enrique (Religious Studies, Theology and Philosophy - Book Archive 2000-2006., 2002)
Legal and Political Philosophy , edited by Enrique Villanueva, is the first volume in the series Social, Political, and Legal Philosophy , published by Rodopi also under his editorship. It contains six original essays by leading political philosophers and philosophers of law (Waldron, Coleman, Postema, Shapiro, Sayre-McCord, and Kraus), along with critical papers on those essays, and replies. This is cutting edge work that elicits sharp responses already as it is published, with the debate joined as the authors reply. Social, Political, and Legal Philosophy is a new book series, edited by Enrique Villanueva, and published by Rodopi Publishers as part of Rodopi Philosophical Studies . The series will publish collections of new essays on topics in social or political or legal philosophy. New volumes will be published approximately every year or every other year.